SAT0004 Is the association sjÖgren'syndrome-spondylarthropathy fortuitous?. (1st June 2001) - di Fazano, C Scotto; Quennesson, E; Quennesson, S; Grilo, RM; Couaral, D; Vergne, P; Bonnet, C; Bertin, P; Treves, R
Abstract : Background: Secondary Sjögren's syndrome is known to occur with rheumatoid arthritis, systemic lupus erythematosus, but apart from a few cases, has not been reported with spondylarthropathy (SpA). Objectives: To determine the prevalence of Sjögren's syndrome in spondylarthropathy patients. Methods: Patients with SpA (n = 62) with inflammatory back pain and/or peripheral arthritis were diagnosed as Ankylosing Spondylitis (AS), undifferentiated SpA (uSpA), psoriatic Arthritis (PA), and arthritis associated with inflammatory bowel diseases (IBD). The investigation of sicca symptoms in the group SPD and healthy controls (n = 102) was based on a valited questionnaire. Patients with SpA with sicca symptomes and/or positive antinuclear antibodies (ANA) were investigated for Sjögren's syndrome by minor salivary gland biopsy. In the spondylarthropathy group, the laboratory variables were: HLA B27, HLA DR, DQ, anti ENA, serology CMV, EBV, HIV, hepatitis B, C. Results: In 17/62 SpA patients (11 uSpA, 5 AS, 1 PA, 17 females, 1 male) Sjögren's syndrome diagnosis by the european criteria indicated a frequency of 27, 4%. Of 62 SpA, 12 were ANA positive (19, 3%), of whom 5 had Sjögren's syndrome. ANA were detected in 8/17(47%) patients with Sjögren's syndrome. Of 62 SpA, 20 had sicca symptoms (32, 2%), compared to 3 of 102(2, 9%) controls. HLA B27 is positive in 12/17 patients (70, 5%). The results of HLA DR, DQ seems to show an high frequency of HLA DR4, and DQ3 in the association group but the results are not significative. Conclusion: The frequency of Sjögren's syndrome is 27, 4%in the spondylartropathy group, thus more than in controls. Thus, the association seems to be not fortuitous. And it's interesting to see more females in a group with more undifferentiated spondylarthropathy: 16/17 are females.